A Meta-Analysis of the Efficacy of Behavioral Interventions to Reduce Risky Sexual Behavior and Decrease Sexually Transmitted Infections in Latinas Living in the United States. (December 2015) - Althoff, Meghan D.; Grayson, Cary T.; Witt, Lucy; Holden, Julie; Reid, Daniel; Kissinger, Patricia
The objective of this meta-analysis was to determine the effect of behavioral interventions in reducing risky sexual behavior and incident sexually transmitted infections (STI) among Latina women living in the United States. Studies were found by systematically searching the MEDLINE, EMBASE, and PsychInfo databases without language restriction. Two independent reviewers screened abstracts and full texts of articles to find randomized control trials testing the effects of behavioral interventions aimed at changing risky sexual behavior among Latinas. Articles were selected using prespecified inclusion criteria. Two independent reviewers extracted data from the included trials in duplicate using a standardized data extraction form. Six randomized control trials met the inclusion criteria for a total of 2, 909 participants. Using random effects models with inverse variance weighting, we found a protective effect of the behavioral intervention on reported risky sexual behavior (odds ratio = 0.52; 95% confidence interval = 0.42, 0.64) and on incident nonviral STI (odds ratio = 0.65; 95% confidence interval = 0.46, 0.93). Behavioral interventions targeted toward Latina populations are effective in reducing risky sexual behaviors and incident STI and should be considered by policymakers as a potential tool for HIV/STI prevention in this population.